Preliminary results of testing a solar air heater equipped with turbulators - Zukowski, Miroslaw; Woroniak, Grzegorz (International Conference “Environmental Engineering”, 2017)
The paper presents the thermal performance of a newly designed device for preheating ventilation air. This new type of a solar air collector is equipped with turbulators to increase heat exchange and eventually to obtain more energy from the Sun. Support elements of this type have not yet been implemented in such heat exchangers. The panel has the following dimensions: width – 0.97 m, length – 1.9 m, thickness – 0.1 m, the area where solar radiation enters the collector – 1.49 m2. Air flow through the exchanger is forced by two radial high flow fans, typically used to cool down servers. The test stand beside the collectors is equipped with an inlet and outlet temperature data recorder and an anemometer to control the air flow rate through the collector. Meteorological data such as solar radiation, wind speed and ambient temperature is obtained from a weather station. The parameters of the working installation have been analysed through the monitoring of measurement variables collected on one-minute time intervals from April to September 2016. The measurement results have been used to determine the thermal performance of the air solar collector of this type. The results of the energy analysis have shown the validity of such an installation.
Keywords: solar air heater; turbulators; renewable energy sources; thermal performance